Genome-wide identification and in silico analysis of GSTs reveals hormone mediated stress response in saffron - Bano, Muqaddas; Li, Xingnuo; Liu, Fang; Ali, Ahmad; Siddiqi, Ejaz Hussain; Zhang, Aidi; Zhang, Xiujun (Frontiers in Plant Science, 2026)
Glutathione S-transferases (GSTs) are multifunctional enzymes in plants that facilitate stress management, detoxification of deleterious chemicals, and transport of secondary metabolites. This research performed a genome-wide examination of Crocus sativus (saffron) and discovered 29 GST genes, each possessing conserved N-terminal and C-terminal domains essential for their functionality. Phylogenetic study categorized these genes into subfamilies, including Tau, Phi, Theta, and Lambda, elucidating evolutionary tendencies unique to saffron. Structural research revealed many motifs and domains within the GST family, whereas chromosomal mapping demonstrated gene clustering, suggesting that gene duplication facilitated the growth of this gene family. Analysis of gene promoters identified regulatory regions that respond to hormones such as methyl jasmonate and abscisic acid, indicating the involvement of GSTs in stress reactions. Subcellular localization predictions indicated that the majority of GSTs are situated in the cytoplasm, with a few located in chloroplasts or vacuoles, highlighting their diverse functions. Structural modeling of a representative GST protein showed a two-subunit structure with distinct regions for binding and catalyzing reactions, validated by a high-quality model score and interactions with a test compound (S-hexylglutathione). This study provides a comprehensive analysis of the GST gene family in saffron, elucidating their structure, evolution, and activities. These insights establish a foundation for future research on the contributions of GSTs to stress tolerance and the synthesis of valuable compounds such as crocin and safranal, which may enhance saffron productivity.